The relationship between organizational context, LMX (Leader-Member Exchange) differentiation, team processes and team effectiveness: a study among nurses in Malaysia - Farah Lina, Azizan (2019)
In the healthcare industry, teamwork is a critical element in assuring patients' safety and quality of care. The aim of this study was to investigate the relationship between organizational context, LMX differentiation and team processes on team effectiveness among nurses in Malaysian public hospitals. The team processes served as a mediator on the relationship between LMX differentiation and team effectiveness. Social Exchange Theory (SET) and Balance Theory were utilized in developing the primary research framework. A total of 214 nursing teams from eleven general hospitals in Malaysia had participated in this study. Hierarchical regression analyses were conducted to test the hypotheses of direct relationships while the PROCESS macro was used to analyze the mediator effect. The results found that only one dimension of organizational context (management process) were significantly related to team effectiveness (team performance, team satisfaction, team viability, team OCB). The findings also revealed that LMX differentiation was significantly related to all dimensions of team effectiveness except team performance. The findings revealed that there is no mediating effect of team processes on the relationship between LMX differentiation and team performance. However, team coordination has mediated the relationship between LMX differentiation and team satisfaction and team viability. Group potency was found to mediate the relationship between LMX differentiation and team viability and team OCB. In conclusion, this study suggests that the leader should assist team members towards an effective teamwork environment. This study also contributes to new literature of team and leadership theories.